2004
DOI: 10.5034/inquiryjrnl_41.1.21
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Evaluating Safety-Net and other Community-Level Factors on Access for Low-Income Populations

Abstract: The framework presented in this article extends the Andersen behavioral model of health services utilization research to examine the effects of contextual determinants of access. A conceptual framework is suggested for selecting and constructing contextual (or community-level) variables representing the social, economic, structural, and public policy environment that influence low-income people's use of medical care. Contextual variables capture the characteristics of the population that disproportionately rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
122
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 55 publications
0
122
1
Order By: Relevance
“…This interest grew out of concerns that policy and delivery system changes that affected the safety net could adversely affect access to care for the most vulnerable subgroups. This study builds on the findings reported from other population-based multivariate studies investigating geographic variation in access (Davidson et al 2004).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…This interest grew out of concerns that policy and delivery system changes that affected the safety net could adversely affect access to care for the most vulnerable subgroups. This study builds on the findings reported from other population-based multivariate studies investigating geographic variation in access (Davidson et al 2004).…”
mentioning
confidence: 89%
“…This study adapts a conceptual and analytical framework ( Figure 1) to test the effects of community-and individual-level variables on access (Davidson et al 2004). Individual-level characteristics are attributes of the individual that influence whether a person will seek care.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…26 We then created four subgroups, including: (1) We used the conceptual model designed by Aday and Andersen to guide the identification of nine additional covariates that might influence access to care, including: age, race, ethnicity, employment, geographic residence, education, household income as a percent of federal poverty level, health status, and marital status. [28][29][30] In two-tailed, chi-square analyses, each covariate was significantly associated with at least one outcome (p<0.10); thus, all covariates were included in logistic regression models.…”
Section: Variables and Analysesmentioning
confidence: 99%
“…[12][13][14][15][16] Although individual-level factors (e.g., insurance status, income, and race) have been the predominant focus in empirical research on determinants of access to care, 17,18 the role of neighborhood environment has received increasing attention in recent years. Early sociological conceptualizations of access, [19][20][21][22] along with the social-epidemiologic literature on neighborhood health effects, [23][24][25] have suggested ways in which neighborhoods' structural, built, and social attributes can affect access to health care. Neighborhood stratification by race and socioeconomic status (SES) is associated with differentials in the quality of the physical and the social environment, which can, in turn, affect residents' health care-seeking behavior, via two potential mechanisms.…”
mentioning
confidence: 99%